SHARENTING ANAK DIFABEL DI INSTAGRAM - Fauziah Hasanah , Fitria (Program Studi Pendidikan Islam Anak Usia Dini, 2021)
Technological developments present a variety of social networking sites that are used by people for different purposes. One of them is the Instagram social networking site which has many active users. Not only teenagers but also parents actively use Instagram and establish virtual interactions. This study aims to find out which parents do sharenting children with disabilities on Instagram. This research method uses descriptive qualitative, data collection is done by analyzing the Instagram account of parents who share children with disabilities. The analysis was carried out using an existential phenomenological approach. The accounts discussed in this study include @athallahdhia, @adamsautismfamily, @zahratuljannah. The results showed that the Sharenring of children with disabilities led to a network of social participation between families, as a documentary archive of their children's childhood memories that can be easily seen back in the future. Other parties who follow the account feel that they add to a positive understanding of children with disabilities, feel motivated, and are inspired to be good parents.